(Re ou Des) construindo a responsabilidade social corporativa - Innecco, Lucio Otavio (2005)
This research is about CORPORATE SOCIAL RESPONSIBILITY (CSR), an old phenomenon with root on social philanthropy of the XVIII century, that along the last two decades have been achieving eminence on the corporate world, ramifications on Society circuit, Estate, and appropriation of nature resources. In an industrialized, global and complex world, in which the environmental degrading and the social differences govern, and the neo-liberalism collection of ideas establishes, the business-related section should answer to the increasing social and environmental demands that are on international and national schedules. Under the aegis of the CSR, this sector leads to find solutions for these problems. So that, a presumed citizen attitude called responsible gains publicity and is surrounded by controversies. It is mandatory to recognize the origin, the feature, the pertinence, and the extension, and also all the imposed facts and other phenomenon aspects. On this meaning, this is a theoretical research that externalizes how to conceive this phenomenon under a social-environment perspective. Developed under a dialectics approach, it defines its own limits on trying to confine the phenomenon and the correlated aspects on all dimensions. In addition, to impress a systemic view if the first impression grant a privilege to split the question up. To the effect that, it is within the specific objectives to identify and observe carefully all the ideas from historic marks changing in social values and society order and also where this business takes place on the society view, for the subject as a whole or deployment. CSR is recognized as an evaluative process of this concept without spoiling the contextual view of this phenomenon facing all society changes. Identifying its slopes the concepts are typologically divided. Through a permanent effort that considers the diversity vision of the world as a relevant agent, some aspects are pointed out that indicate inconsistency and others that can call positive results not only to business sector, but also to the society. It is found out that both, the insufficiency of the national research about this subject, and also the lack of a renewed conceptual reflection that definitely can integrate the social and environment dimensions. Beneath a conscious and selfless attitude of the company, that implies as a vector of the social legitimating of its actions, the CSR is a result of an energy interaction of the community section. It is neither a sublime attitude, nor a distinguished responsibility from that the laws or social coercion require, because the business is impersonal, it subsists of the opportunities and its primary function is the profit, even though few people disagree. In order that, the attitude cross over the traditional obligation and lives the responsiveness, through witch grow thin the answers to the demands and the sensibility to the opportunity.